Self-Adjusting Fuzzy Logic Based Control of Robot Manipulators in Task Space - Yilmaz, B. Melih; Tatlicioglu, Enver; Savran, Aydogan; Alci, Musa (IEEE transactions on industrial electronics (1982), 2022)
End effector tracking control of robot manipulators subject to dynamical uncertainties is the main objective of this article. Direct task space control that aims minimizing the end effector tracking error directly is preferred. In the open loop error system, the vector that depends on uncertain dynamical terms is modeled via a fuzzy logic network and a self-adjusting adaptive fuzzy logic component is designed as part of the nonlinear proportional derivative based control input torque. The stability of the closed-loop system is investigated via Lyapunov based arguments and practical tracking is proven. The viability of the proposed control strategy is shown with experimental results. Extensions to uncertain Jacobian case and kinematically redundant robots are also presented.